2020
DOI: 10.26418/positron.v10i1.37739
|View full text |Cite
|
Sign up to set email alerts
|

Sintesis TiO2 terdoping Fe3+ untuk Degradasi Rhodamin B Secara Fotokatalisis dengan Bantuan Sinar Tampak

Abstract: Fotokatalis TiO2 terdoping Fe3+ telah disintesis menggunakan titanium tetraisopropoksida (TTIP) sebagai prekursor serta dopan Fe3+ dari Fe(NO3)3 dengan metode sol-gel. Fotokatalis TiO2 didoping menggunakan Fe3+ bertujuan untuk memperlebar serapan dari sinar Ultra Violet (UV) hingga sinar tampak pada berbagai variasi persentase Fe3+ 0,05%; 0,125%; 0,25% (b/v). karakterisasi fotokatalis dilakukan dengan metode spektrofotometri UV-Vis/DRS, FT-IR, XRD  dan diuji aktivitasnya terhadap degradasi rhodamin B. Hasil pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…After visible light irradiated for 120 min, the OD600 value of Fe-TiO2/kaolinite is much lower than TiO2/kaolinite and TiO2, where arise to 0.01 and 0.23, respectively. It may be an indication that the formation of photogenerated electronhole pairs on the surface of Fe-TiO2/kaolinite is easier to occur than TiO2 when absorbing visible light because it has a smaller band gap as a result of the mixing of the Fe 2p with Ti 2p orbitals [16][17][18]. These results are consistent with the absorption spectra.…”
Section: Photocatalytic Activity As Antibacterial Escherichia Colisupporting
confidence: 78%
See 3 more Smart Citations
“…After visible light irradiated for 120 min, the OD600 value of Fe-TiO2/kaolinite is much lower than TiO2/kaolinite and TiO2, where arise to 0.01 and 0.23, respectively. It may be an indication that the formation of photogenerated electronhole pairs on the surface of Fe-TiO2/kaolinite is easier to occur than TiO2 when absorbing visible light because it has a smaller band gap as a result of the mixing of the Fe 2p with Ti 2p orbitals [16][17][18]. These results are consistent with the absorption spectra.…”
Section: Photocatalytic Activity As Antibacterial Escherichia Colisupporting
confidence: 78%
“…The TiO2 and Fe-doped TiO2 nanoparticle was prepared by sol-gel method using titanium isopropoxide (TTIP) as titanium precursor. Preparation of Fe-doped-TiO₂ sol was carried out according to our previous report [17]. Briefly, 7.5 mL of TTIP and 26.5 mL of ethanol were mixed simultaneously into 2 mL acetic acid and 2 mL distilled water and put in a reflux flask then added 1 mL acetylacetone.…”
Section: Preparation Of Tio2 and Fe-doped Tio2 Solmentioning
confidence: 99%
See 2 more Smart Citations
“…Absorption at wave numbers 696-718 cm -1 was a stretching vibration of Ti-O [29,30]. TiO 2 and SCDs/TiO 2 composites were observed for absorption peaks at wave number 412 cm -1 as a characteristic of Ti-O stretching vibration [24] [6]. The results showed that the combination of SCDs with TiO 2 does not cause a shift in the titanium oxide absorption peak.…”
Section: Ft-ir Spectrophotometrymentioning
confidence: 99%